2023
DOI: 10.24272/j.issn.2095-8137.2023.062
|View full text |Cite
|
Sign up to set email alerts
|

Hiding on jagged karst pinnacles: A new microendemic genus and species of a limestone-dwelling agamid lizard (Squamata: Agamidae: Draconinae) from Khammouan Province, Laos

Saly Sitthivong,
Peter Brakels,
Santi Xayyasith
et al.

Abstract: We describe a unique new species and genus of agamid lizard from the karstic massifs of Khammouan Province, central Laos. Laodracon carsticola Gen. et sp. nov. is an elusive medium-sized lizard (maximum snout-vent length 101 mm) specifically adapted to life on limestone rocks and pinnacles. To assess the phylogenetic position of the new genus amongst other agamids, we generated DNA sequences from two mitochondrial gene fragments (16S rRNA and ND 2) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Lyu et al ( 2023 ) proposed a new 10-genus classification for the Asian horned toad subfamily Megophryinae based on phylogenetic relationships and morphological differences and further reviewed the taxonomic history of Asian horned toad species in China. Sitthivong et al ( 2023 ) described a new microendemic genus and species of a limestone-dwelling agamid lizard (Squamata: Agamidae: Draconinae) from Laos, which was read more than 16 000 times within three weeks of its online publication, representing the most viewed ZR paper published in 2023. Qiu et al ( 2023 ) identified and described eight subspecies of mainland Apis cerana , providing insights into their evolutionary history and subspecies boundaries to enable customized conservation strategies for both widespread and endemic honeybee populations, thereby informing colony introduction and breeding strategies.…”
mentioning
confidence: 99%
“…Lyu et al ( 2023 ) proposed a new 10-genus classification for the Asian horned toad subfamily Megophryinae based on phylogenetic relationships and morphological differences and further reviewed the taxonomic history of Asian horned toad species in China. Sitthivong et al ( 2023 ) described a new microendemic genus and species of a limestone-dwelling agamid lizard (Squamata: Agamidae: Draconinae) from Laos, which was read more than 16 000 times within three weeks of its online publication, representing the most viewed ZR paper published in 2023. Qiu et al ( 2023 ) identified and described eight subspecies of mainland Apis cerana , providing insights into their evolutionary history and subspecies boundaries to enable customized conservation strategies for both widespread and endemic honeybee populations, thereby informing colony introduction and breeding strategies.…”
mentioning
confidence: 99%